HUBUNGAN PERILAKU PETUGAS KEBERSIHAN DENGAN TINDAKAN PENANGANAN LIMBAH PADAT (Studi di RSUD Syarifah Ambami Rato Ebu Bangkalan Tahun 2018) - Dwi Shinta N; Sri Mardoyo; Marlik . (Poltekkes Kemenkes Surabaya, 2018)
Solid waste, these could be medical solid waste and non-medical solid waste. The solid waste need to be treated according to hospital’s solid waste management in Indonesia which regulated by Kepmenkes 1204 2004. The regulation was made to control environmental impact and the transmission of disease in the hospital. The janitors as the officer who directly handling solid waste management must have a good knowledge and attitute so it will affect their act. The aim of this study is to know the effect of janitor’s behavior to act of handling the solid waste management in RSUD Syamrabu BangkalanThe type of this study was analytical observational study using cross sectional design. Data were taken by observed the waste management and interviewed the janitors to understand their knowledge and attitude to the solid waste management. There were 49 janitors who were used as samples. Samples was taken using simple random sampling. Data then analysed by univariate and bivariate test using kendall tau as statistic test.The results showed that most of the janitors who have good knowledge good attitude were 77.55% while enough act were 63.2%. there is janitor’s knowledge and their act to handling medical solid waste. The janitors knowledge and attitude were good, but their act to handling medical solid waste need to be improved.The hospital should provide strict regulations regarding the handling of solid waste and training or socialization should be held for janitors about handling solid waste regularly.Keywords: hospital, janitor, solid waste management